KELIMPAHAN, KEANEKARAGAMAN DAN BIOMASSA IKAN KARANG PADA PERAIRAN UJONG PANCU, KABUPATEN ACEH BESAR - M Rizki Fazillah; Taisir Afrian; Nanda Muhammad Razi; Maria Ulfah Ulfah; Samsul Bahri (Universitas Teuku Umar, 2020)
Reef fish utilize coral reef ecosystems as a place to live, foraging, spawning and nurturing. This study aims to determine the abundance of species, diversity and biomass of reef fish found in the waters of Ujong Pancu, Aceh Besar district. This research was conducted in October 2017, there were 5 research location. Data was collected using the Underwater Visual Census (UVC) method. The result show that the highest abundance of reef fish was found in waters of Lhok Mata Ie with a value of 5311.71 Ind/ ha. While the lowest abundance of reef fish was found in Tuan Island waters with a value of 896.67 Ind/ ha. Overall diversity of Ujong Pancu waters reefs is included in the medium-high category. The highest average biomass of reef fish is found in the water of East Batee Island with a value of 100.69 Kg/ ha. While the lowest average biomass of reef fish is found in the waters of West Batee Island with a biomass value 23.87 Kg/ ha. Keywords : Abundance, biomass, diversity, reef fish, Ujong Pancu